Tinapay ng buhay [videorecording] : simbahan at kahirapan - Hukom, Dave; Gabe Mercado (Quezon City : Jesuit communications, 2003)
Inverstigates the problem of poverty that continues to ail our countryand frustrate our church. It poses the question of poverty in the light of church teaching and action, and seeks to shed some light on this seemingly insoluble problem.
Keywords: Catholic church -- Philippines; Religion and politics -- Philippines